2014
DOI: 10.1080/00140139.2014.960010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hip belt use and load placement in a backpack on postural stability and perceived exertion: a within-subjects trial

Abstract: The purpose of this study was to assess the effects of hip belt use and load placement in a backpack on perceived exertion and postural stability. Thirty participants were instructed to stand on a force plate and walk along a designated route under five conditions: unloaded, high-load placement, low-load placement, hip belt on and hip belt off. The average velocity and sway area from the force plate were measured. Participants also rated their perceived stability and exertion. Compared to the unloaded conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…In this way, according to the categorization of gait phases (Perry and Burnfield, 2010), our study showed that walking while carrying a backpack could be related to the inefficiency of weight-bearing stability (loading response phase), limb progression and limb advancement (pre-swing phase and terminal swing phases). Supporting these results, previous studies found that carrying a backpack decreased postural stability during walking (Yen et al, 2011) and standing (Golriz et al, 2014;Pau and Pau, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…In this way, according to the categorization of gait phases (Perry and Burnfield, 2010), our study showed that walking while carrying a backpack could be related to the inefficiency of weight-bearing stability (loading response phase), limb progression and limb advancement (pre-swing phase and terminal swing phases). Supporting these results, previous studies found that carrying a backpack decreased postural stability during walking (Yen et al, 2011) and standing (Golriz et al, 2014;Pau and Pau, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with previous research, we did not identify differences in overall RPE between the high and low load placement conditions [18,19,37,38], which contradicts the finding of Stuempfle et al [7], who reported high load placement as being the most desirable backpack placement on the spine. Unlike the overall RPE, the shoulder region RPE was greater during the high load placement condition as compared to low load placement.…”
Section: Discussionsupporting
confidence: 84%
“…Compared to the unloaded condition, some studies showed no significant effects of load on walking speed with loads up to 20% BM [ 47 ], whereas a significant decrease was observed with loads up to 40% BM in other studies [ 7 ]. However, a significant increase was found at loads of 20–35% BM load [ 44 , 50 ]. In all studies, loads ranged from 20–40% BM, with no clear trend in the effects as load increased or decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found no difference in neck and shoulders comfort based on load placement, but only on load entity (15 to 40% BM, compared with 0%) [ 24 , 69 , 70 ]. In the last stand, it was reported that the rate of perceived exertion (RPE) was significantly lower when the BP was worn with the support of a hip belt [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation